Natural intraepithelial lymphocyte populations rise during necrotic enteritis in chickens - Majeed, Shuja; Hamad, Shaimaa K.; Shah, Bikas R.; Bielke, Lisa; Nazmi, Ali (Frontiers in Immunology, 2024)
Intraepithelial lymphocytes (IEL) reside in the epithelium at the interface between the contents of the intestinal lumen and the sterile environment of the lamina propria. Because of this strategic location, IEL play a crucial role in various immunological processes, ranging from pathogen control to tissue stability. In mice and humans, IEL exhibit high diversity, categorized into induced IEL (conventional CD4 and CD8 T cells) and natural IEL (TCRCD8, TCR, and TCRneg IEL). In chickens, however, the subpopulations of IEL and their functions in enteric diseases remain unclear. Thus, we conducted this study to investigate the role of IEL populations during necrotic enteritis (NE) in chickens. At 14 days of age, sixty-three Specific-pathogen-free (SPF) birds were randomly assigned to three treatments: Control (sham challenge), Eimeria maxima challenge (EM), and Eimeria maxima + Clostridium Perfringens (C. Perfringens) co-challenge (EM/CP). The EM and EM/CP birds were infected with Eimeria maxima at day 14 of age, and EM/CP birds were additionally orally inoculated with C. perfringens at days 18 and 19 of age. Birds were weighed at days 18, 20, and 26 of age to assess body weight gain (BWG). At 20 days of age (1 day-post C. perfringens infection; dpi), and 26 days of age (7 dpi), 7 birds per treatment were euthanized, and jejunum was harvested for gross lesion scores, IEL isolation, and gene expression. The EM/CP birds exhibited subclinical NE disease, lower BWG and shorter colon length. The Most changes in the IEL populations were observed at 1 dpi. The EM/CP group showed substantial increases in the total number of natural IEL subsets, including TCRαβ+CD4-CD8-, TCRαβ+CD8αα+, TCR+, TCRneg and innate CD8 (iCD8 cells by at least two-fold. However, by 7 dpi, only the number of TCRαβ+CD4-CD8- and TCRβ+CD8+ IEL maintained their increase in the EM/CP group. The EM/CP group had significantly higher expression of proinflammatory cytokines (IL-1 and IFN-) and Osteopontin (OPN) in the jejunum at 1 dpi. These findings suggest that natural IEL with innate and innate-like functions might play a critical role in the host response during subclinical NE, potentially conferring protection against C. perfringens infection.